2002
DOI: 10.1021/jp026351c
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Infrared Spectrum and Aromaticity of the Al2(CO)2 Molecule

Abstract: The reaction products between aluminum atoms and CO molecules in solid neon have been studied by matrix isolation infrared spectroscopy and quantum chemical calculations. Besides the previously reported AlCO and Al(CO) 2 molecules, new absorption at 1727.9 cm -1 was also produced and assigned to a dibridged Al 2 (CO) 2 molecule based on isotopic substitution experiments and theoretical frequency calculations. High level ab initio computations indicated that the Al 2 (CO) 2 molecule has a singlet ground state w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Tsipis et al studied aromaticity in the series of cyclo-Cu n H n (n = 3-6), 16 cyclo-M n H n (M = Ag, Au; n = 3-6), 17 cyclo-Au 3 L n H 3-n (L = CH 3 , NH 2 , OH, Cl; n = 1-3), 18 cyclo-Cu n Ag 3-n H n (n = 1-3), cyclo-Cu n Ag 4-n H n (n = 1-4), and cyclo-Cu n Ag 5-n H n (n = 1-5). 19 Tsipis et al [15][16][17][18][19] stated that the planar structures with the equivalent M-M and M-H (M-L) bonds is an indication of the aromatic character of these species. They supported their claim of the presence of aromaticity in the metallocycles by high binding energies, negative values of the NICS index and the calculated electrophilicity index o. Tsipis et al [15][16][17][18][19] concluded that these metallocycles exhibit a composite bonding mode involving s-, pand dcomponents.…”
Section: Aromaticity and Antiaromaticity Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsipis et al studied aromaticity in the series of cyclo-Cu n H n (n = 3-6), 16 cyclo-M n H n (M = Ag, Au; n = 3-6), 17 cyclo-Au 3 L n H 3-n (L = CH 3 , NH 2 , OH, Cl; n = 1-3), 18 cyclo-Cu n Ag 3-n H n (n = 1-3), cyclo-Cu n Ag 4-n H n (n = 1-4), and cyclo-Cu n Ag 5-n H n (n = 1-5). 19 Tsipis et al [15][16][17][18][19] stated that the planar structures with the equivalent M-M and M-H (M-L) bonds is an indication of the aromatic character of these species. They supported their claim of the presence of aromaticity in the metallocycles by high binding energies, negative values of the NICS index and the calculated electrophilicity index o. Tsipis et al [15][16][17][18][19] concluded that these metallocycles exhibit a composite bonding mode involving s-, pand dcomponents.…”
Section: Aromaticity and Antiaromaticity Inmentioning
confidence: 99%
“…19 Tsipis et al [15][16][17][18][19] stated that the planar structures with the equivalent M-M and M-H (M-L) bonds is an indication of the aromatic character of these species. They supported their claim of the presence of aromaticity in the metallocycles by high binding energies, negative values of the NICS index and the calculated electrophilicity index o. Tsipis et al [15][16][17][18][19] concluded that these metallocycles exhibit a composite bonding mode involving s-, pand dcomponents. This conclusion was disputed by Zubarev et al, 43 who on the basis of the valence atomic occupations 4s 0.56 3d 9.91 4p 0.02 obtained in NBO analysis for the Cu atom in planar Cu 4 H 4 (D 4h , 1 A 1g ) suggested that aromaticity in Cu n H n clusters is neither of pnor d -but rather of s-nature.…”
Section: Aromaticity and Antiaromaticity Inmentioning
confidence: 99%
“…Obviously, with the increasing number of the Si atom, the cyclic structures become increasingly important. It is worth mentioning that structures of Al 2 CO, Ga 2 CO, and In 2 CO observed in solid argon 36–38 are very similar to those of isomers 1 1 and 3 1 . Similarly, the ground states of other Si 2 ‐containing tetra‐atomic species, such as Si 2 C 2 39, 40, Si 2 CN 41, Si 2 CP 42, are all cyclic forms (see Table IV).…”
Section: Resultsmentioning
confidence: 53%
“…The reaction between Al atoms and CO molecules in solid Ne have been investigated by IR spectroscopy. 126 Besides the previously reported AlCO and Al(CO) 2 molecules a new absorption is seen at 1727.9 cm À1 which is assigned to the dibridged Al 2 (CO) 2 molecule. This molecule has D 2h symmetry and shows considerable aromatic properties with two completely delocalised p-electrons.…”
Section: Group 13mentioning
confidence: 65%